2009
DOI: 10.1007/s11191-009-9206-6
|View full text |Cite
|
Sign up to set email alerts
|

Articulation of Conceptual Knowledge and Argumentation Practices by High School Students in Evolution Problems

Abstract: The oral arguments of 12th grade students while solving tasks related to evolution are examined. Two groups (N = 45), taught by the same teacher, were studied during a complete teaching sequence. The paper focuses on data from the last sessions, devoted to solving problems in small groups, problems related to different dimensions of the evolutionary model. Data include video recordings, the students' written productions and the researcher (first author) field notes. The objective is to examine the process of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Organizing classrooms around argumentation encourages students to interact directly with each other, as opposed to directing conversation exclusively to the teacher, who, in turn, evaluates comments (Berland, 2011;Duschl & Osborne, 2002;Martin & Hand, 2009). Making argumentation structures visible to students encourages them to make their ideas explicit, promoting the elaboration, connection, and consolidation of scientific understandings (Bell & Linn, 2000;Chin & Osborne, 2010;de Lima Tavares, Jiménez-Aleixandre, & Mortimer, 2010;Keys, Hand, Prain, & Collins, 1999;von Aufschnaiter et al, 2008). Some studies have shown that, over time, students appear to use more of the desired components and scientific norms in their argumentation (McNeill et al, 2006;Osborne et al, 2004;Sampson, Enderle, Grooms, & Witte, 2013).…”
Section: Implications and Critiquesmentioning
confidence: 99%
“…Organizing classrooms around argumentation encourages students to interact directly with each other, as opposed to directing conversation exclusively to the teacher, who, in turn, evaluates comments (Berland, 2011;Duschl & Osborne, 2002;Martin & Hand, 2009). Making argumentation structures visible to students encourages them to make their ideas explicit, promoting the elaboration, connection, and consolidation of scientific understandings (Bell & Linn, 2000;Chin & Osborne, 2010;de Lima Tavares, Jiménez-Aleixandre, & Mortimer, 2010;Keys, Hand, Prain, & Collins, 1999;von Aufschnaiter et al, 2008). Some studies have shown that, over time, students appear to use more of the desired components and scientific norms in their argumentation (McNeill et al, 2006;Osborne et al, 2004;Sampson, Enderle, Grooms, & Witte, 2013).…”
Section: Implications and Critiquesmentioning
confidence: 99%
“…The results of their study show that students' engagement of argumentation enables them to use their prior knowledge and elaborate their understanding of science at high levels of abstraction. de Lima Tavares et al (2010) conducted a research with 45 twelfth-grade students in two classes to examine the articulation of conceptual knowledge about evolution and argumentation practices, documented in the use of evidenced claims at different epistemic levels. In their study, they argue that students' conceptual knowledge about evolution helps them to construct arguments and vice versa, that is, students' engagement in argumentative discourse promotes their understanding of evolution concepts.…”
Section: Argumentation and Conceptual Understanding 1141mentioning
confidence: 99%
“…Duschl and Osborne () argue that an absence of dialogical argumentation in the classroom could result in a reduction in science learning. Research has demonstrated the positive effect of argumentation on understanding of science concepts and improving reasoning skills in elementary school children (Mason, ; Mercer, Dawes, Wegerif, & Sams, ; Simon & Maloney, ), high school students (de Lima Tavares, Jiménez‐Aleixandre, & Mortimer, ; Jiménez‐Aleixandre, Rodrìguez, & Duschl, ; Zohar & Nemet, ), and college students (Aydeniz, Pabuccu, Cetin, & Kaya, ). These studies employed qualitative analysis of student utterances during argumentation or quantitative pre/post‐test designs to explore students' knowledge gain.…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%